Compassion-Focused Intervention for Highly Self-Critical Individuals: Pilot Study. Issue 5 (13th June 2018) - Rose, Alexandra; McIntyre, Ruth; Rimes, Katharine A.
Abstract : Self-criticism is a transdiagnostic process associated with a range of psychological problems. This uncontrolled pilot study evaluated the feasibility and acceptability of a six-session intervention using methods from compassion-focused therapy to reduce self-criticism, as well as investigating changes in a range of outcome measures. Twenty-three university student participants with significant impaired functioning associated with high levels of self-criticism received six individual weekly treatment sessions and a 2-month follow-up appointment. Acceptability was assessed through participant feedback. The intervention appeared to be feasible in terms of recruitment and retention of participants, and participant feedback indicated that overall the intervention seemed acceptable. There were statistically significant improvements between pre- and post-intervention for self-criticism, functional impairment, mood, self-esteem and maladaptive perfectionism with medium to large effect sizes at both post-intervention and follow-up. Gains were maintained or increased between post-treatment and 2-month follow-up. The study showed preliminary evidence of effectiveness of a compassion-focused intervention for self-critical students which appeared to be a feasible and acceptable treatment approach. This intervention now requires investigation in a randomized controlled trial.